HYGIENE DAN KESEHATAN LINGKUNGAN - Siti Rokayah; Gunawan Widjaja (Cross-border, 2022)
This research aims to analyze the Hygiene and Health Environment. This research is normative juridical research that is descriptive in nature and uses a prescriptive form with the aim of problem-solving. The data used is secondary data which was analyzed qualitatively. The results of this study indicate that the definitions and regulations governing Hygiene and Health Environment overlap each other.